Gambaran penggunaan ponsel pintar sebagai faktor risiko nyeri kepala primer pada mahasiswa angkatan 2013 Fakultas Kedokteran Universitas Sam Ratulangi Manado - Oroh, Kezia; Pertiwi, Junita M.; Runtuwene, Theresia (Universitas Sam Ratulangi, 2016)
Abstract: The aim of this research is to get a description of smart phone usage as a factor of primary headache to the students of medical faculty year 2013 Sam Ratulangi Unifersity of Manado. This research is a kind of descriptive research by approach of latitude cut. Received data are from primary data using questioner. From 243 of the total respondent there are 72 male respondents and 171 female respondents, with the percentages of each primary headache as follows: tension-type headache 72.84%, migraine without aura 17.28%, migraine with aura 8.64% and cluster headache 1.23%. The most usage feature of the smart phone user is social media (40.16%). The length of smart phone usage is 5 to 7 hours a day (47.33%). 64.61% of the respondents that using a smart phone experienced an eye ache. 48.98% of the respondents are those who do physic activities less than two times during fifteen minutes or more in one week. 48.56% of the respondents are using the smart phones with 30 degree neck declivity. Respondents who are using smart phones experienced tension-type headache is 75.71%, migraine without aura 16.43% , migraine with aura 7.15% and cluster headache 0.71%.Keywords: primary headache, smart phonesÂ Abstrak: Penelitian ini bertujuan untuk mendapatkan gambaran penggunaan ponsel pintar sebagai faktor risiko nyeri kepala primer pada mahasiswa angkatan 2013 fakultas kedokteran Universitas Sam Ratulangi. Jenis penelitian ini deskriptif dengan pendekatan potong lintang. Data yang didapat melalui data primer menggunakan kuesioner. Dari total 243 responden, diperoleh 72 responden laki-laki dan 171 responden perempuan, dengan presentase untuk setiap jenis nyeri kepala primer adalah sebagai berikut: nyeri kepala tipe tegang 72.84%, migren tanpa aura 17.28%, migren dengan aura 8.64% dan nyeri kepala klaster 1.23%. Fitur yang sering digunakan pada ponsel pintar adalah sosial media (40.16%). Lama penggunaan ponsel pintar 5-7 jam dalam sehari (47.33%). 64.61% dari responden yang menggunakan ponsel pintar terdapat keluhan mata. 48.98% dari responden adalah mereka yang melakukan aktivitas fisik < 2x selama > 15 menit dalam seminggu. 48.56% responden menggunakan ponsel pintar dengan kemiringan leher 30o. Responden yang menggunakan ponsel pintar dan mengeluhkan nyeri kepala tipe tegang 75.71%, migren tanpa aura 16.43%, migren dengan aura 7.15% dan klaster 0.71%. Kata kunci: nyeri kepala primer, ponsel pintar